Composition and Structure of Oyster Adhesive Reveals Heterogeneous Materials Properties in a Biological Composite. (16th August 2016) - Metzler, Rebecca A.; Rist, Rebecca; Alberts, Erik; Kenny, Paul; Wilker, Jonathan J.
Abstract : Oyster reefs help maintain coastal ecosystems by filtering water, holding silt in place, and absorbing storm surge energy. We are just beginning to understand the chemical and structural nature of the adhesive used by these animals for building such reef communities. The adhesive has a high calcium carbonate content relative to other bioadhesives, but also appreciable levels of organics, presumably for bonding. The studies presented here use X‐ray absorption near edge structure spectroscopy, X‐ray photoemission electron microscopy, scanning electron microscopy, and microhardness methods to understand the composition, as well as the mechanical properties, of this biological material. Oyster adhesive appears to be a heterogeneous mixture of calcium carbonate and silica inclusions arranged randomly within a matrix that lacks any observable structure. Microindentation shows inclusions are significantly harder than their surroundings. This hard plus soft strategy has been noted in other biological materials, although not in any adhesives. These compositional and structural insights help propose a mechanism by which the animals generate their adhesive. Such an intriguing structure, along with resulting mechanical implications, may help explain how oyster reefs can thrive despite being subjected to demanding forces created by predators and the environment around them. Abstract : X‐ray photoemission electron microscopy polarization dependent imaging contrast and microindentation of the Crassostrea virginica adhesive–shell boundary show the adhesive is an unstructured composite consisting of hard inclusions within a soft matrix. The shells on either side have multicrystalline calcite prisms of varied structure and significantly greater hardness than the average adhesive.